2022
DOI: 10.21809/rilemtechlett.2022.162
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on magnesium silicate hydrate phases and future opportunities

Abstract: This short letter summaries the latest research on the structure and thermodynamic modelling of the magnesium silicate hydrates (M-S-H) phases. M-S-H structure is comparable to hydrated clays, with a smaller and rounder microstructures compared to clay platelets. Similar to clay minerals, M-S-H can incorporate ions such as aluminium and hydrated exchangeable cations to compensate the negative surface charge. This fundamental understanding of M-S-H structure allowed to develop structure-based thermodynamic mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…The two major MgO-based cements include magnesium silicate and magnesium carbonate cement. The former binds based on magnesium silicate hydrate (MSH) 19 while hydrous carbonate-containing brucite 20 accounts for the binding in the latter. MSH has an amorphous (nanocrystalline) layered silicate structure with tetrahedral layers as in phyllosilicate minerals 21,22 .…”
Section: Binding Phases In Different Cementsmentioning
confidence: 99%
“…The two major MgO-based cements include magnesium silicate and magnesium carbonate cement. The former binds based on magnesium silicate hydrate (MSH) 19 while hydrous carbonate-containing brucite 20 accounts for the binding in the latter. MSH has an amorphous (nanocrystalline) layered silicate structure with tetrahedral layers as in phyllosilicate minerals 21,22 .…”
Section: Binding Phases In Different Cementsmentioning
confidence: 99%
“…MS cements harden due to the formation of magnesium silicate hydrate (M-S-H) phases from the hydration of reactive sources of magnesia and silicate [38,76]. MS cement produced by calcination and pulverization of magnesium silicate rocks and lime were patented at the end of the 19 th century [77].…”
Section: Magnesium Silicate (Ms) Cementsmentioning
confidence: 99%
“…Further U.S. patents indicated that magnesia chloride cements were improved by the addition of silicates [78,79]. In general, poorly crystalline M-S-H forms from the reaction between silicate and magnesia, Mg(OH) 2 , MgSO 4 or MgCl 2 in a basic environment [76,80]. M-S-H formation is also observed in geological environment in the presence of high pH values (>9) in the contact zone between Portland cement and Mg-containing solution [81]: M-S-H has been observed in cements in contact with river [82], clayey [83] or saline waters [84,85] (Equation 3a) also forming during the serpentinization of olivine [86,87] (Equation 3b).…”
Section: Magnesium Silicate (Ms) Cementsmentioning
confidence: 99%
“…It forms at a lower pH than Portland cements and is a promising matrix for storage of nuclear waste [ 16 , 17 ]. According to Bernard [ 18 ], binders containing M-S-H also have good mechanical properties, a dense microstructure and potentially good resistance to leaching. Thus, M-S-H is currently of interest as an environmentally friendly alternative to Portland cement due to its potentially lower carbon footprint [ 3 ] and for the encapsulation of nuclear waste [ 19 ].…”
Section: Introductionmentioning
confidence: 99%